P17-07 In vitro approaches for inhalation safety assessment of poorly soluble and insoluble materials - L. Scott; J. Kelsall; E. Tha; L. Ma-Hock; R. Landsiedel; V. Hutter (Toxicology Letters, 2025)

Determination of chlorinated paraffins and olefins in plastic consumer products of the Swiss market - O. Mendo Diaz; A. Tell; S. Hangartner; J. Hutter; U. Stalder; H. Friedl; A.M. Buser; S. Kern; L. Bigler; D. Bleiner; N.V. Heeb (Chemosphere, 2025)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

P15-17 In vitro immune off-target toxicity assessment using morph_ONE for parenterally administered antibody-drug conjugate test item - B. Ghiot; E. Hoffman; J. Kelsall; A. Saeed; R. Mahendran; L. Scott; V. Hutter (Toxicology Letters, 2024)

High content analysis of in vitro alveolar macrophage responses can provide mechanistic insight for inhaled product safety assessment - V. Hutter; S. Hopper; J. Skamarauskas; E. Hoffman (Toxicology in Vitro, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Nephrotoxicity and Kidney Transport Assessment on 3D Perfused Proximal Tubules - Marianne K. Vormann; Linda Gijzen; Simon Hutter; Lisette Boot; Arnaud Nicolas; Angelique van den Heuvel; Jelle Vriend; Chee Ping Ng; Tom T. G. Nieskens; Vincent van Duinen; Bjorn de Wagenaar; Rosalinde Masereeuw; et al. (The AAPS Journal, 2018)

Combining Extracellular miRNA Determination with Microfluidic 3D Cell Cultures for the Assessment of Nephrotoxicity: a Proof of Concept Study - Laura Suter-Dick; L. Mauch; D. Ramp; M. Caj; M. K. Vormann; S. Hutter; H. L. Lanz; J. Vriend; R. Masereeuw; M. J. Wilmer (The AAPS Journal, 2018)

Explaining Andean megadiversity: the evolutionary and ecological causes of glassfrog elevational richness patterns - Carl R. Hutter; Juan M. Guayasamin; John J. Wiens (Ecology Letters, 2013)
The Tropical Andes are an important global biodiversity hotspot, harbouring extraordinarily high richness and endemism. Although elevational richness and speciation have been studied independently in some Andean groups, the evolutionary and ecological processes that explain elevational richness patterns in the Andes have not been analysed together. Herein, we elucidate the processes underlying Andean richness patterns using glassfrogs (Centrolenidae) as a model system. Glassfrogs show the widespread mid‐elevation diversity peak for both local and regional richness. Remarkably, these patterns are explained by greater time (montane museum) rather than faster speciation at mid‐elevations (montane species pump), despite the recency of the major Andean uplift. We also show for the first time that rates of climatic‐niche evolution and elevational change are related, supporting the hypothesis that climatic‐niche conservatism decelerates species' shifts in elevational distributions and underlies the mid‐elevation richness peak. These results may be relevant to other Andean clades and montane systems globally.

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Sex recognition in zebrafish (Danio rerio) - Sophie Hutter; Sarah M. Zala; Dustin J. Penn (Journal of Ethology, 2011)

Silphinene Sesquiterpenes as Model Insect Antifeedants - Azucena González-Coloma; Fernando Valencia; Nuria Martín; Joseph J. Hoffmann; Louis Hutter; J. Alberto Marco; Matías Reina (Journal of Chemical Ecology, 2002)

Flow cytometric determinations of cellular substances in algae, bacteria, moulds and yeasts - K. -J. Hutter; H. E. Eipel (Antonie van Leeuwenhoek, 1978)